Taḥlīlu al Syakhṣiyyāti fī filmi al Rasūmi al Mutaḥarrikati Ballerina li Eric Summer wa Eric Waren - Aminor, Aminor; Sudiarti, Sri (Al-Uslub: Journal of Arabic Linguistic and Literature, 2021)
Character Analysis in Ballerina Animated Film Directed by Eric Summer And Eric Waren (Literary Studies).The purpose of this research is to find out the characters and some of the characters in the animated film Ballerina directed by Eric Summer and Eric Warin, and to be able to know the values contained in the animated film. The type of research used is qualitative research. The source of the research data is the animated film ballerina by Eric Summer and Eric Warin. The object of this research is a character in the animated film Ballerina by Eric Summer and Eric Warin published by Aifan Sharthok's YouTube channel. The data collection techniques used are by witnessing and recording techniques. The instrument used is the author assisted with text data, stationery and laptop. The method used to analyze data is a description of the analysis.